A efetividade da execução por quantia certa contra a fazenda pública - Simão, Ana Paula (2009)
The constitutional reform introduced with the Constitutional Amendment 45/2004 occasioned a deep transformation in the execution process effective until then in the Brazilian legal system. This happened by means of the modification of the matter relating to ordinary law rule on the subject, with the objective to obtain a more rapid process and the delivery of life asset as an accomplishment in an effective manner. Nevertheless, despite the modification introduced with Constitutional Amendment 45/2004, the execution against Public Treasury was not affected by any alteration, remaining, in full, the legal devices that examine the affair. The execution against the Public Treasury possesses peculiarities, which are justified due to the prerogatives granted to it aiming public interest, primordial for the maintenance of the State and its functions. The main peculiarity resides in the impossibility of constriction of the public goods, which tries the debit payment by means of the entitled payment notice to government. The judicial payment notice to government must observe the budgetary rules and a money order, under the risk of the Public Administration to suffer the impounding of public revenues. The impounding of public revenues is an exceptional measure, which occurs when some of the constitutional hypotheses are present. The jurisprudence still admits the impounding of public revenues in another hypothesis, not listed in the Federal Constitution. This hypothesis is the one which the subject creditor suffers from disease and requires urgently an amount for its survival. The non-effectiveness of the impounding of public revenues, ahead of the economic impossibility of the Federation being for effectual of the judicial sentence, is common. It is the entitled theory of the reserve of the possible. What is observed by the present work study is that the execution system in face of the Public Treasury does not reach its objective, mainly because the non-payment of judicial payment notice to government does not mean any more severe punishment. Attempting to solve the problem, there are reform projects. In our point of view, the proposals are shy ahead of the chaos established in the system of debits payments of the Public Treasury. This is the reason why we propose a more intense modification, as in the case of other countries, with the constriction of the dominical public good